A Behavioural Model of E-Banking Usage in Italy. (19th June 2013) - Capece, Guendalina; Campisi, Domenico
E-banking is defined as the automated delivery of new and traditional banking products and services directly to customers through electronic, interactive communication channels. "Pure online" banks are characterized by the absence of physical windows and front-office personnel. Traditional banks are still integrating traditional distribution channels with online ones; the scenario is therefore still evolving over time. Despite the intrinsic potentialities, Italy is far from being a leader in the usage of innovative online instruments in the banking system and will struggle with new innovation waves. In this paper, we measure the potential effective e-banking usage. Furthermore, we investigate the behaviour of users and adopters, identifying the major causes influencing satisfaction and usage and the impact of these different causes on the intensity of utilization. The analysis is based on a panel of 495 real users, thus allowing the profiling of the Italian adopter to discover the causes of usage and outline strategies for the growth of e-banking services in Italy.